Analisis Audit atas Siklus Pendapatan dalam Menilai Efektivitas Sistem Pengendalian Internal pada Exmo Tea Cafe - Ardiansa Ardiansa; Andiqarina Andiqarina; Masyhuri Masyhuri (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
Internal control is a crucial aspect for SMEs in maintaining the reliability of revenue recording and preventing the risk of misappropriation. This study aims to analyze the implementation of internal control in the revenue cycle at Exmo Tea Café and to evaluate its effectiveness through internal audit. The research uses a qualitative descriptive approach with data collection through interviews with management personnel directly involved in transactions and financial recording. The analysis is conducted using the COSO framework, which includes five main components: control environment, risk assessment, control activities, information and communication, and monitoring. The research results indicate that Exmo Tea Café has implemented several basic elements of internal control, such as recording transactions through a cashier application, daily cash reconciliation, and reporting to the owner. However, the effectiveness of these controls is still limited because the segregation of duties between receiving and recording is not optimal, risk assessment is reactive, documentation and report archiving are not systematic, and monitoring is conducted informally. In addition, there are no formal policies regarding operational standards (SOPs) or internal audit procedures that could serve as guidelines for continuous control implementation. These conditions have the potential to lead to risks of fraud, recording errors, and delays in financial reporting. Therefore, these findings underscore the need for a comprehensive enhancement of the internal control system, including strengthening the separation of duties, conducting preventive risk assessments, providing employee training related to financial governance, as well as implementing more formal monitoring and documentation. These improvements are expected to increase reporting accuracy, operational effectiveness, and minimize the potential for errors or fraud in the company's financial activities.